Multidisciplinary Canadian consensus on the multimodal management of high-risk and radioactive iodine-refractory thyroid carcinoma - Ezzat, Shereen; Pasternak, Jesse D.; Rajaraman, Murali; Abdel-Rahman, Omar; Boucher, Andrée; Chau, Nicole G.; Chen, Shirley; Gill, Sabrina; Hyrcza, Martin D.; Lamond, Nathan; Massicotte, Marie-Hélène; Winquist, Eric; et al. (Frontiers in Oncology, 2024)
Most follicular cell-derived differentiated thyroid carcinomas are regarded as low-risk neoplasms prompting conservative therapeutic management. Here, we provide consensus recommendations reached by a multidisciplinary group of endocrinologists, medical oncologists, pathologists, radiation oncology specialists, a surgeon and a medication reimbursement specialist, addressing more challenging forms of this malignancy, focused on radioactive iodine (RAI)-resistant or -refractory differentiated thyroid carcinoma (RAIRTC). In this document we highlight clinical, radiographic, and molecular features providing the basis for these management plans. We distinguish differentiated thyroid cancers associated with more aggressive behavior from thyroid cancers manifesting as poorly differentiated and/or anaplastic carcinomas. Treatment algorithms based on risk-benefit assessments of different multimodal therapy approaches are also discussed. Given the scarcity of data supporting management of this rare yet aggressive disease entity, these consensus recommendations provide much needed guidance for multidisciplinary teams to optimally manage RAIRTC.